Artificial intelligence for patent prior art searching. (March 2021) - Setchi, Rossitza; Spasić, Irena; Morgan, Jeffrey; Harrison, Christopher; Corken, Richard
Abstract: This study explored how artificial intelligence (AI) could assist patent examiners as part of the prior art search process. The proof-of-concept allowed experimentation with different AI techniques to suggest search terms, retrieve most relevant documents, rank them and visualise their content. The study suggested that AI is less effective in formulating search queries but can reduce the time and cost of the process of sifting through a large number of patents. The study highlighted the importance of the humanin-the-loop approach and the need for better tools for human-centred decision and performance support in prior art searching.